Software de tutorías vía web para la carrera de Tecnología en Electrónica modalidad semipresencial del Área de la Energía, las Industrias y los Recursos Naturales no Renovables mediante la transmisión de audio y video asincrónico. - Palacios Montalván, Ketty Delfina (2008)
The advance of science and technology now allows other education that is known as Virtual Education, which is to study from home via computer connected to the Internet. The application developed is oriented to this type of education and consists of several modules that allow the Career Technology Electronics become known more in this application through the Information, Create a Curriculum and monitoring of system users, Create a Calendar academic, Registration their students, and most importantly support the process of tutoring through forums module and the module tutorials which have been created and adjusted according to the requirements of the race, the latter being the principal of system where you can attach documents as support material and videos for students to download the same and develop their tasks. The purpose of the application is to make the process easy and convenient tutoring schedule that the user has to receive it, thus supporting the formation of new professionals in terms of excellence and quality are concerned.